Electrochemical synthesis of nanostructured gold film for the study of carbohydrate–lectin interactions using localized surface plasmon resonance spectroscopy. (20th March 2015) - Bhattarai, Jay K.; Sharma, Abeera; Fujikawa, Kohki; Demchenko, Alexei V.; Stine, Keith J.
Graphical abstract: Highlights: Two potential step electrodeposition of novel block-like gold nanostructures. Nanostructured gold surface produced has good LSPR response. Suitable for real-time assay of lectin–carbohydrate interactions in mixed SAMs. Nanostructured surface can be easily regenerated for subsequent re-use. Abstract: Localized surface plasmon resonance (LSPR) spectroscopy is a label-free chemical and biological molecular sensing technique whose sensitivity depends upon development of nanostructured transducers. Herein, we report an electrodeposition method for fabricating nanostructured gold films (NGFs) that can be used as transducers in LSPR spectroscopy. The NGF was prepared by electrodepositing gold from potassium dicyanoaurate solution onto a flat gold surface using two sequential controlled potential steps. Imaging by scanning electron microscopy reveals a morphology consisting of randomly configured block-like nanostructures. The bulk refractive index sensitivity of the prepared NGF is 100 ± 2 nm RIU −1 and the initial peak in the reflectance spectrum is at 518 ± 1 nm under N2 (g). The figure of merit is 1.7. In addition, we have studied the interaction between carbohydrate (mannose) and lectin (Concanavalin A) on the NGF surface using LSPR spectroscopy by measuring the interaction of 8-mercaptooctyl-α-d -mannopyranoside (αMan-C8 -SH) with Concanavalin A by first immobilizing αMan-C8 -SH in mixed SAMs with 3, 6-dioxa-8-mercaptooctanol (TEG-SH) on the NGF surface. The interaction of Con A with the mixed SAMs is confirmed using electrochemical impedance spectroscopy. Finally, the NGF surface was regenerated to its original sensitivity by removing the SAM and the bound biomolecules. The results from these experiments contribute toward the development of inexpensive LSPR based sensors that could be useful for studying glycan–protein interactions and other bioanalytical purposes.